A Comment on "A Systematic Review and Meta-Analysis of the Evidence on Learning During the COVID-19 Pandemic" - Nino Buliskeria; Ali Elminejad; Tomas Havranek; Zuzana Irsova; Stepan Jurajda; Marek Kapicka; Martina Luskova (Institute for Replication (I4R), 2025)
Betthäuser et al. (2023) examine the effects of the COVID-19 pandemic on the learning progress of school-aged children. They collect 291 estimates from 42 studies. Their meta-analysis-corrected estimate implies a substantial decline in students' learning (Cohen's d = -0.14, 95% confidence interval -0.17 to -0.10). First, we successfully reproduce the main results and the majority of supporting figures. Second, we provide additional analysis addressing publication bias by implementing correction techniques: PET-PEESE (funnelbased), 3PSM (selection model), and RoBMA (model averaging). Additionally, we implement novel approaches that account for the strength of biased selection favoring affirmative results in the sample of analyzed studies. Third, we use techniques that assume the presence of p-hacking (MAIVE, RTMA). Using these methods, the corrected effect ranges from -0.25 to -0.11 with high statistical significance. While our analysis does reveal some evidence of selection bias in underlying data (primary studies), these phenomena do not appear to systematically distort the overall findings of the original study.
https://doi.org/10.17605/osf.io/u8gaz
Keywords: I21; I24; I28; C68; 330; Replication; Robustness; Meta-analysis; COVID-19; Education; Learning deficit